Is the Model Theory of Planned Behavior Relevant to Measure the Intention of Students in Klaten Regency to Start an Initial Business? Model Theory of Planned Behavior, Measure the Intention - SriNugroho, arifjulianto; Haris, Abdul; Heru Murjito; Agung Nugroho Jati; Imam Santoso; Anna Febrianty S (Universitas Muhammadiyah Surakarta, 2022)
The research objective is to test the model whether the variables of entrepreneurial competence, subjective norms and self-efficacy have a positive influence on the early pioneering entrepreneurial intentions and behavior of students in the Klaten Regency. Early pioneering businesses is a business in a critical period emerging potency of loss and bankruptcy. The research design was carried out using a quantitative method which explains the causal relationship of one dependent variable influenced by three independent variables and one mediating variable. Hypothesis test was formulated in the model using multivariate test. The research population is all private university students in the Klaten Regency area who have started their early pioneering business. The sampling technique was carried out by purposive sampling as many as 110 respondents The quantitative test of the model using Structural Equation Modeling (SEM) obtained the results that there is a positive relationship between entrepreneurial competence, self-efficacy and intention to entrepreneurial behavior. Meanwhile, one independent variable in the form of subjective norms does not significantly influence. Future research can expand the model through testing intentional antecedents of behavior by developing moderating variables